Techniques in plant telomere biology - Fajkus, Jirí; Sýkorová, Eva; Leitch, Andrew R (BioTechniques, 2005)
The role model systems have played in understanding telomere biology has been enormous, and understanding has rapidly transferred to human telomere research. Most work using model organisms to study telomerase and nontelomerase-based telomere-maintenance systems has centered on yeasts, ciliates, and insects. But it is now timely to put considerably more effort into plant models for a number of reasons: (i) the rice and Arabidopsis genome sequencing projects make data mining possible; (ii) extensive collections of insertion mutants of Arabidopsis thaliana enable phenotypic effects of protein gene knockouts to be analyzed, including for those genes involved in telomere structure, function (including, for example, in meiosis), and maintenance; and (iii) the variability of plant telomeres is considerable and ranges from the telomerase-mediated synthesis of the Arabidopsis-type (TTTAGGG) and vertebrate-type (TTAGGG) repeats to sequences synthesized by telomerase-independent mechanism(s) that are still to be discovered. Here we describe how the understanding of telomere biology has been advanced by methods used to isolate telomeric sequences and prove that the putative sequences isolated are indeed telomeric. We show how assays designed to prove the activity of telomerase [e.g., telomeric repeat amplification protocol (TRAP)] lead not only to an understanding of telomere structure and function, but also to the understanding of cell activity in development and in the cell cycle. We review how assays designed to reveal protein/protein and protein/nucleic acid interactions promote understanding of the structure and activities of plant telomeres. Together, the data are making significant contributions to telomere biology in general and could have medical implications.
Keywords: rostliny; Sequence Analysis, DNA; Plants; telomery; buněčné jádro; hybridizace in situ fluorescenční; telomerasa; Cell Nucleus; techniky amplifikace nukleových kyselin; sekvenční analýza DNA; Telomere; geneticky modifikované rostliny; In Situ Hybridization, Fluorescence; DNA, Plant; Telomerase; Plants, Genetically Modified; DNA rostlinná; Nucleic Acid Amplification Techniques